Determination of Flood Susceptibility Index Using Overlay-Scoring Data Method based on Geographic Information System (GIS) in Semarang City, Central Java, Indonesia - Muhammad Rizky Romadhon; Abdul Aziz (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2022)
Semarang City is the capital of the Central Java Province, located in the lowlands and directly adjacent to the north side of the Java Sea. This geographical condition makes this city very vulnerable to being affected by floods. This study aims to determine the distribution of flood-prone locations and classify the level of flood susceptibility that occurs in the Semarang City. Quantitative descriptive is the type of research with an overlay method based on scoring parameters related to environmental conditions. These parameters include slope, soil type, rainfall, altitude, land use and river flow buffers. The scored parameters are then entered into the overlay stage with other parameters in the geographic information system (GIS) application to form a map of the flood susceptibility level. The data analysis technique used the descriptive method. The level of flood susceptibility map resulting from this study is in one area of the Pemali-Juana Sub-watershed. The results also show that the scattered highly vulnerable areas in the northern part of Semarang City are areas with low elevations and flat slopes, then dominated by settlement land use that lacks infiltration areas, small river buffer sizes. These are what make the area classified as an area that is very prone to flooding.